2021
DOI: 10.1109/tii.2020.3011062
|View full text |Cite
|
Sign up to set email alerts
|

Value-Driven Robotic Digital Twins in Cyber–Physical Applications

Abstract: Although the skills of robot manipulators are becoming technically more complex, the unprecedented costeffective access to recently unveiled intelligent robots has the potential to unleash as yet unimagined automation capabilities. A key technology behind this opportunity for companies to gain a competitive edge through an informed and intelligent robotized automation is the robotic digital twin (RDT). As such, the RDT will be instrumental in mirroring targeted properties of a physical robot to obtain a digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Digital Twins technology can be integrated with emerging technologies (e.g., Blockchain) 4 , 5 to ensure confidence, traceability, compliance, authenticity, quality, and security. 6 In academia, this technology has been applied to power electronic converter diagnosis, 7 parallel society and social contact, 8 , 9 dynamic capture of robotic information, 10 digital double-edge networks, 11 and other cutting-edge cross-fields. Kapteyn et al.…”
Section: Introductionmentioning
confidence: 99%
“…Digital Twins technology can be integrated with emerging technologies (e.g., Blockchain) 4 , 5 to ensure confidence, traceability, compliance, authenticity, quality, and security. 6 In academia, this technology has been applied to power electronic converter diagnosis, 7 parallel society and social contact, 8 , 9 dynamic capture of robotic information, 10 digital double-edge networks, 11 and other cutting-edge cross-fields. Kapteyn et al.…”
Section: Introductionmentioning
confidence: 99%
“…The results in Table I showed that bandwidth consumption of the point cloud topic at a frequency of 10Hz is 5530 KB/s, which is 5.53 and 4.02 times greater than the available 2 Video of the experiment: https://youtu.be/dE7NjBsrtKk bandwidths of both wireless and wired configurations. This leads to a network overhead reduction of 0.603 Hz and a 3.337 s delay on average in the receiving of messages, as can be seen in Table I and Table II.…”
Section: Resultsmentioning
confidence: 99%
“…A digital twin is a real-time virtual representation of a physical object or process. Primarily used in simulations and data visualisations during the design and development stage, digital twins have since expanded their scope as vital components of a cyber-physical system [2] [3]. When applied to industrial robots, this includes a digital twin instance of its mechanical and electronic components.…”
Section: Introductionmentioning
confidence: 99%
“…project management [112], robotics [113,114], sustainable development [115,116]. However, in current study will focus on Energy systems.…”
Section: Definitionmentioning
confidence: 99%